Intensity discrimination in individuals with and without cochlear dead regions - H M, Apoorva; S, Kruthika; V, Saranya; K, Rajalakshmi (Journal of All India Institute of Speech and Hearing, 2013)
Objective: The objective of the present study was to analyze intensity discrimination between individuals with and without cochlear dead regions using SISI test. Method: Thirty ears diagnosed as having sensorineural hearing loss were considered for the present study, out of which 15 were individuals without cochlear dead regions and 15 with cochlear dead regions. The age criterion ranged from 20 to 75 years (mean age=55.16 years) and the degree of hearing loss ranged from mild to moderately-severe. The TEN test was administered to detect the presence or absence of cochlear dead regions. Short Increment Sensitivity Index (SISI) was administered to find out the ability of each individual to detect small intensity changes (1 dB increment) at equal sensation levels (SLs). Results: The analysis of the data collected revealed statistically significant difference in SISI scores between the individuals with and without cochlear dead regions, i.e., SISI scores were better in individuals having cochlear dead regions when compared to those without cochlear dead regions. The results also showed significant difference in SISI scores across frequencies in the group with cochlear dead regions and increase in SISI scores with increase in frequency. Conclusion: Cochlear dead region is associated with a better ability for intensity discrimination and this effect may reflect cortical re-organization and over representation induced by the cochlear dead regions.